Changes in organic fractions, cations, and stabilization from feces to fecal sludge: implications for dewatering performance and management solutions - Stanley Bortse Sam; Eberhard Morgenroth; Linda Strande (Journal of Water, Sanitation and Hygiene for Development, 2023)
Reliable dewatering performance remains a key challenge in fecal sludge management, and the controlling factors or mechanisms are not well understood. There remain limited studies on constituents in feces and fecal sludge and how they affect the dewaterability of fecal sludge. This study aimed at evaluating a range of constituents in feces, and to gain empirical knowledge toward a mechanistic understanding of how they influence dewaterability. In this study, cellulose reduced capillary suction time, decreased supernatant turbidity, and increased cake solids. While hemicellulose decreased supernatant turbidity, lignin increased supernatant turbidity, capillary suction time, and cake solids. Extracellular polymeric substances (EPS) increased both capillary suction time and supernatant turbidity and decreased cake solids, whereas lipids increased turbidity. Cations had no significant effect on dewatering properties. Overall, fecal sludge stored in containments had better dewatering performance than ‘fresh’ fecal sludge, which was attributed to stabilization. Field fecal sludge had a higher relative abundance of Pseudomonas, which is associated with better aggregation, and fewer small particles (<10 μm) that clog filters to reduce dewatering performance. Further understanding of stabilization and developing an agreed-upon metrics of stabilization are essential for predicting fecal sludge dewatering performance, and developing smaller footprint dewatering treatment technologies. HIGHLIGHTS Fibers, EPS, and lipids influence the dewatering performance of fecal sludge.; Stabilization plays a key role in improving dewaterability of fecal sludge.; Management practices play a larger role than diet in accumulated fecal sludge.; Variations in the FS microbial community could explain differences in dewaterability.;